El Excentrico, 1959-07-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
July 20, 1959 [20 de julio de 1959]. Ano 9, No. 22. Cover contains a group photo of young Dora Gutierrez with her parents. At the time that this photo was taken, Gutierrez was celbrating her quinceañera, a coming of age celebration that are often held for latino girls. The headline reads, "Miss Dora Gutierrez. 15 years of age was presented in Society."